Future Campus 2019
DOI: 10.4324/9780429346750-19
|View full text |Cite
|
Sign up to set email alerts
|

Briefing and Design for Sustainability

Abstract: The design process had to take into account the budget constraints as well as the interdisciplinary nature of the project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The methodology used to derive the typology differs from previous attempts ( Philip & Spratt, 2007 ; Simon & Eby, 2003 ; Sipe & Rogers, 1999 ) and ensures that the typology is grounded in participants' descriptions of programmes. This typology differs from previous typologies in the UK ( Ford, 1998 ; Philip & Hendry, 1996 ; Philip & Spratt, 2007 ) in that it allows each programme, despite variation in their format, delivery and a range of other characteristics, to be allocated to one and only one mentoring model. Consistent with previous studies ( Mass Mentoring Partnership, 2007 ; Sipe & Rogers, 1999 ), this study revealed that a total of 33 different categories can be used to differentiate between existing programmes, spanning across programme structures and formats, detailed information on mentees and mentors involved and organizational details and practices.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The methodology used to derive the typology differs from previous attempts ( Philip & Spratt, 2007 ; Simon & Eby, 2003 ; Sipe & Rogers, 1999 ) and ensures that the typology is grounded in participants' descriptions of programmes. This typology differs from previous typologies in the UK ( Ford, 1998 ; Philip & Hendry, 1996 ; Philip & Spratt, 2007 ) in that it allows each programme, despite variation in their format, delivery and a range of other characteristics, to be allocated to one and only one mentoring model. Consistent with previous studies ( Mass Mentoring Partnership, 2007 ; Sipe & Rogers, 1999 ), this study revealed that a total of 33 different categories can be used to differentiate between existing programmes, spanning across programme structures and formats, detailed information on mentees and mentors involved and organizational details and practices.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple studies have attempted to form typologies in the field of mentoring, for instance, to differentiate between types of relationships between mentor and mentee ( Langhout, Rhodes, & Osborne, 2004 ; Pryce & Keller, 2007 ; Simon & Eby, 2003 ) different types of mentors ( Ford, 1998 ; Scanlon, 2009 ) or to summarise negative mentoring experiences ( Simon & Eby, 2003 ). Classifying different types of mentoring relationships was the aim of Karcher and Nakkula's work, who distinguished mentoring relationships by looking at the focus, the purpose and the authorship and what is termed the ‘developmental’ and ‘instrumental’ style of relationships ( Karcher & Nakkula, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…supporting the person with care needs to go out for a couple of hours) were not always considered appropriate uses of time. It has been suggested that a truly 'strengths-based' approach requires whole system change to the way support is provided, shifting attitudes and priorities of both those receiving and delivering services towards greater collaboration [54] The range of different services discussed in our field work (Table 2) is evidence of the complicated system within which families may be needing, seeking and/or receiving support, and within which practitioners are working. Systems theory has been used to understand and examine complex interventions, and how to evaluate them, and has been applied to service environments such as those we are discussing here, where multiple services (for example social work, education, mental health and voluntary sector organisations) and multiple individuals may be involved and affected.…”
Section: Plos Onementioning
confidence: 97%